Prominent early adulthood hyperferritinemia in scrub typhus - Naskar, Sayan; Chaudhuri, Bhaskar Narayan; Basak, Amrita; Guchhait, Partha; Das, Satadal (International Journal of Advances in Medicine, 2024)
Background: Scrub typhus is an acute infectious disease, caused by Orientia tsutsugamushi. It is endemic to a geographically distinct region of Japan, Taiwan, China, and South Korea, known as the tsutsugamushi triangle, as well as in Nepal, Pakistan, and Papua New Guinea. In India, the incidence of this disease varies from 4-46% with high morbidity and mortality. Methods: In this cross-sectional study at a tertiary care hospital in Kolkata, India we analysed ferritin blood levels along with different demographic and laboratory test parameters of 60 suspected scrub typhus patients who were also scrub typhus IgM antibody positive during a one-year study period. Results: It was found that serum ferritin levels were unusually high in 21-40 years age group patients along with mildly increased urea and creatinine levels. Other important findings were below 40 years of age males were mostly affected, but above 40 years of age, females were generally affected. Haemoglobin and platelet levels were normal in all age groups. Although WBC count and neutrophils were normal in the 21-40 years age group, in other age groups increased levels were observed. CRP, SGPT, and SGOT levels were uniformly high above 20 years of age. Electrolytes were mildly decreased. Conclusions: It appears that oxidative stress-induced acute kidney injury may be an important reason for the rising ferritin levels in the 21-40 years age group. These important findings may be helpful to clinicians in management of these patients.